The first hydrographic and forest survey of the Mucuri Valley in the 19th century (International Journal of Geoscience, Engineering and Technology, 2025)
In 1836, the landlord Antônio da Costa Pinto, taking into account the interests of the Brazilian Empire, ordered the engineer Pierre Victor Renault to make a survey of the forests of Mucuri and the Todos os Santos River in order to choose a place for the construction of a colony and also due to interest in research on the mineral resources in the region. This expedition concluded in 1837 and produced a report that significantly enhanced regional knowledge of the Mucuri Valley. During his journey of clearing certain areas of Minas Gerais, in the region of the present Valley of Mucuri, he discovered a new river that the natives called Mokury, which was later definitively named Rio Mucuri. Found valuable minerals along the route of the Todos os Santos River, chrysolite, seawater, and withdrew from the banks of the small stream called Americanas. Among these, there was a beryl of two and a half pounds, which King John VI presented to the French Emperor Napoleon I, and which is in the Louvre Museum, in the form of a cup. This expedition resulted in a report that contributed to a greater regional knowledge of the Mucuri Valley.
Keywords: Mucuri Valley; Hydrographic survey; Todos os Santos River; Mucuri River